Imaging copper metabolism imbalance in Atp7b (-/-) knockout mouse model of Wilson's disease with PET-CT and orally administered 64CuCl2. - Peng F; Lutsenko S; Sun X; Muzik O; Peng, Fangyu; Lutsenko, Svetlana; Sun, Xiankai; Muzik, Otto (Molecular Imaging & Biology, 2012)
Objectives: This study aims to determine the feasibility and utility of functional imaging of copper metabolism imbalance in Atp7b (-/-) knockout mouse model of Wilson's disease (WD) with positron emission tomography-computed tomography (PET-CT) using orally administered copper-64 chloride ((64)CuCl(2)) as a tracer.Procedures: Atp7b (-/-) KO mice (N = 5) were subjected to PET scanning using a hybrid PET-CT scanner, after oral administration of (64)CuCl(2) as a tracer. Time-dependent PET quantitative analysis was performed to assess gastrointestinal absorption and biodistribution of (64)Cu radioactivity in the Atp7b (-/-) KO mice, using C57BL wild-type (WT) mice (N = 5) as a normal control. Estimates of human radiation dosimetry were calculated based on biodistribution of (64)Cu radioactivity in live animals.Results: PET-CT analysis demonstrated higher (64)Cu radioactivity in the liver of Atp7b (-/-) knockout mice compared with that in the control C57BL WT mice (p < 0.001), following oral administration of (64)CuCl(2) as a tracer. In addition, (64)Cu radioactivity in the lungs of the Atp7b (-/-) knockout mice was slightly higher than those in the control C57BL WT mice (p = 0.01). Despite initially higher renal clearance of (64)Cu, there was no significant difference of (64)Cu radioactivity in the kidneys of the Atp7b (-/-) KO mice and the control C57BL WT mice at 24 h post-oral administration of (64)CuCl(2) (p = 0.16). There was no significant difference in low (64)Cu radioactivity in the blood, brain, heart, and muscles between the Atp7b (-/-) knockout mice and control C57BL WT mice (p > 0.05). Based on the biodistribution of (64)Cu radioactivity in C57BL WT mice, radiation dosimetry estimates of (64)Cu in normal human subjects were obtained. An effective dose (ED) of 42.4 μSv/MBq (weighted dose over 22 organs) was calculated and the lower large intestines were identified as the critical organ for radiation exposure (120 μGy/MBq for males and 135 μGy/MBq for females). Radiation dosimetry estimates for patients with WD, derived from the biodistribution of (64)Cu in Atp7b (-/-) KO mice, showed a slightly lower ED of 37.5 μSv/MBq, with the lower large intestines as the critical organ for radiation exposure (83 μSv/MBq for male and 95 μSv/MBq for female).Conclusions: PET-CT quantitative analysis demonstrated an increased level of (64)Cu radioactivity in the liver of Atp7b (-/-) KO mice compared with that in the control C57BL WT mice, following oral administration of (64)CuCl(2) as a tracer. The results of this study suggest the feasibility and utility of PET-CT using orally administered (64)CuCl(2) as a tracer ((64)CuCl(2)-PET/CT) for functional imaging of copper metabolism imbalance in WD.